2021
DOI: 10.1096/fj.202100355rrr
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in glucose metabolism in adult male offspring of maternal mice fed diets supplemented with inulin via regulation of the hepatic long noncoding RNA profile

Abstract: Maternal overnutrition during pregnancy and lactation is an important risk factor for the later development of metabolic disease, especially diabetes, among mothers and their offspring. As a fructan-type plant polysaccharide, inulin has prebiotic functions and is widely used as a natural antidiabetic supplement. However, to date, the mechanism of maternal inulin treatment in the livers of offspring has not been addressed, especially with respect to long noncoding RNAs (lncRNAs).In this study, female C57BL6/J m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…The observed reduction in blood insulin content and the consistent levels of glucagon and glucose in this study suggest that inulin attenuates insulin secretion from pancreatic β-cells Miao et al reported that 3.33 and 1.67 g/kg/day inulin supplementation signi cantly reduced blood glucose and insulin levels in gestational diabetes mellitus mice [24]. Similar results were reported by Zhang et al [25]that blood glucose and insulin levels in high-fat mice were signi cantly reduced when supplemented with 2 g/kg of inulin. However, blood glucose concentrations were comparable between the two groups in this study, suggesting that goats maintained a stable range of blood glucose to maintain their body and cellular function when inulin was supplemented.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed reduction in blood insulin content and the consistent levels of glucagon and glucose in this study suggest that inulin attenuates insulin secretion from pancreatic β-cells Miao et al reported that 3.33 and 1.67 g/kg/day inulin supplementation signi cantly reduced blood glucose and insulin levels in gestational diabetes mellitus mice [24]. Similar results were reported by Zhang et al [25]that blood glucose and insulin levels in high-fat mice were signi cantly reduced when supplemented with 2 g/kg of inulin. However, blood glucose concentrations were comparable between the two groups in this study, suggesting that goats maintained a stable range of blood glucose to maintain their body and cellular function when inulin was supplemented.…”
Section: Discussionsupporting
confidence: 90%
“…However, blood glucose concentrations were comparable between the two groups in this study, suggesting that goats maintained a stable range of blood glucose to maintain their body and cellular function when inulin was supplemented. The discrepancy in the blood glucose content might be due to the difference in the variety and physiological stage, and the health status of animals [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of lncRNA MEG3 induces endothelial dysfunction in HUVECs of IVF‐born offspring (Jiang et al., 2021 ). In rats, overnutrition of pregnant dams alters hepatic lncRNAs in male offspring (Zhang et al., 2021 ). Moreover, accumulating evidence suggests that lncRNAs are involved in the regulation of placental development and function (McAninch et al., 2017 ), which may have the potential to influence fetal development and program the fetus for diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the parental intake of five functional food oils has been shown to modulate miRNA expression in both the parent and offspring [47]. In addition, functional foods have also been shown to modulate the expression of lncRNA in parents and offspring [38,[48][49][50]. Essentially, in T2D, changes in the expression of non-coding RNAs have been observed in genes involved in insulin secretion and glucose metabolism, leading to alterations in their function [51,52].…”
Section: Overview Of Epigenetic Changes Associated With T2dmentioning
confidence: 99%